(untitled) (Bangladesh Journal of Infectious Diseases, 2024)
Background: Infertility is a global health issue implicated to sociocultural, environmental, health care practice and genetic factors in both male and female individuals. Oligozoospermic and azoospermic conditions reported to be associated with Y chromosome microdeletions (YCDs) in various loci. Objective: The purpose of the present study was to investigate Y chromosome microdeletions in azoospermic individuals attending fertility clinics, focusing on the SRY239, SRY242, and SRY254 alleles. Methodology: This cross-sectional study was conducted in the Department of Physiology and Molecular Biology at Bangladesh University of Health Sciences, Dhaka, Bangladesh involving 20 infertile males. Appropriate procedures were followed to address ethical aspects. Demographic and clinical data were collected using structured questionnaire. One milliliter blood sample was collected for DNA extraction and downstream analysis. AZFc markers SY239, SY242 and SY254 alleles were determined by standard polymerase chain reaction (PCR). Data were expressed as number (percent) and figures as appropriate. A value < 0.05 was taken as level of significant. Results: Age (years) range of the 20 adult infertile azoospermic male was 25-50 with mean (±SD) 39 ±8. Of the 20 subjects 15 (75%) was smoker, 5 (25%) hypertensive and 2 (10%) diabetic. By profession their distribution includes day labors 4 (20%), businessman 8 (40%), garments workers 4 (20%), hawker 2 (10%) and teacher 2 (10%). Among 2 (10%) garments workers show their AZFc fragments deletions. Of the 20 men, azoospermia factor region (AZFc) SRY239 and SRY254 allele deletion were present in 4 individuals. The AZFc variant allele SRY242 was normal in all 20 men. Of the 4 individual present the SRY239 and SRY254 2 were obese. Conclusion: Y-chromosome microdeletion AZFc region allele markers SRY239 and SRY254 are present in azoospermic male but the AZFc SRY242 was of wild type. Presence of candidate allele detection did not show any relationship with study variables possibly due to small number of samples. To reach conclusive finding of AZFc mutations affecting male infertility, study need to be confirmed by recruiting substantial number of cases and carrying out the investigation at the early stage. Bangladesh Journal of Infectious Diseases, June 2024;11(1):22-29